Inverted Papilloma Originating Primarily from the Nasolacrimal Duct: A Case Report and Review of the Pertinent Literature - Hussein Z. Walijee; Sandeep Berry; Stuart Quine; Carol Lane; Daniel S. Morris; Benedict Bowman (Case Reports in Otolaryngology)
Introduction. Inverted papilloma (IP) is an uncommon, benign yet aggressive neoplasm characterised by high recurrence rates and tendency towards malignant transformation. The majority of IP cases originate in the ethmoid region, lateral wall of the nasal fossa, and maxillary sinus. The authors report a case of an IP originating primarily from the nasolacrimal duct (NLD). Case. A 69-year-old Caucasian gentleman presented with a lump in his right medial canthal region, epiphora, and discharge bilaterally. Radiological investigation revealed a well-defined, heterogeneous mass within the proximal NLD eroding the bony canal, protruding into the middle meatus and into the right orbit. The tumour was excised en bloc utilizing a combined external and endoscopic approach based on its location. Histology revealed hyperplastic ribbons of basement membrane-enclosed epithelium growing endophytically into the underlying stroma with no evidence of invasive malignancy. The patient made an uneventful recovery with unchanged visual acuity and normal extraocular movements. Conclusion. The case demonstrates variability within the sinonasal tract that IP can develop and the individuality of each case necessitating tailored operative techniques for complete excision whilst minimising recurrence rates. We also present a combined endoscopic approach for the en bloc resection of a NLD IP with no clinical recurrence at 15-month follow-up.